2019
DOI: 10.22270/jddt.v9i1-s.2398
|View full text |Cite
|
Sign up to set email alerts
|

Inulin: A promising carrier for controlled and targeted drug delivery system

Abstract: The delivery of a drug to the preferred site of action is referred to as drug targeting. The benefits of drug targeting are a reproducible and controlled release rate of the therapeutic compound, which forestalls overdose. Due to the potential to treat colonic diseases with minimum side effects, colon targeting has become of high interest over the last decades. Inulin was investigated for its potential as encapsulation material regarding its enzymatic degradability and its drug release behaviour. Inulin is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…RS, whose chemical structure is similar to that of the glucan coating layer, has been reported as a fermentable carbohydrate in the colon and produced short-chain fatty acids (e.g., acetic, propionic, and butyric acids). , Similar to RS, the granular structure of the α-glucan-coated NCS encapsulant was resistant to hydrolysis after incubating in the digestion fluids and retained its intact form with the protective α-glucan coating through preventing attack by digestive enzymes. Carbohydrate-based encapsulation materials such as RS, alginates, inulin, and dextran, which are hard to digest in the small intestinal environment, can be successfully delivered into the colon without affecting their form, and after reaching the colon, they can be broken down by the microbiota. On the other hand, the NCS control could be easily disintegrated with a greater hydrolysis rate (Figure B). It was seen that the α-glucan coating layer, which was formed using Np AS with a reaction time of 12 h, on the starch granule was partially removed by the digestion fluid while it was tightly bound to the granule surface when the Np AS reaction was carried out for 48 h. As discussed above and shown in Table , the chain-elongated glucan structure is more stable, which restricts the physical accessibility of amylolytic digestive enzymes, and this property can be utilized to make it a potential colon-specific delivery carrier with a microbe-assisted release system during the passage through the small intestinal environment while preserving its capsulated form.…”
Section: Resultsmentioning
confidence: 99%
“…RS, whose chemical structure is similar to that of the glucan coating layer, has been reported as a fermentable carbohydrate in the colon and produced short-chain fatty acids (e.g., acetic, propionic, and butyric acids). , Similar to RS, the granular structure of the α-glucan-coated NCS encapsulant was resistant to hydrolysis after incubating in the digestion fluids and retained its intact form with the protective α-glucan coating through preventing attack by digestive enzymes. Carbohydrate-based encapsulation materials such as RS, alginates, inulin, and dextran, which are hard to digest in the small intestinal environment, can be successfully delivered into the colon without affecting their form, and after reaching the colon, they can be broken down by the microbiota. On the other hand, the NCS control could be easily disintegrated with a greater hydrolysis rate (Figure B). It was seen that the α-glucan coating layer, which was formed using Np AS with a reaction time of 12 h, on the starch granule was partially removed by the digestion fluid while it was tightly bound to the granule surface when the Np AS reaction was carried out for 48 h. As discussed above and shown in Table , the chain-elongated glucan structure is more stable, which restricts the physical accessibility of amylolytic digestive enzymes, and this property can be utilized to make it a potential colon-specific delivery carrier with a microbe-assisted release system during the passage through the small intestinal environment while preserving its capsulated form.…”
Section: Resultsmentioning
confidence: 99%
“…90 Inulin could also act as a carrier agent, and its use has become increasingly popular in recent years. 91 Moreover, a previous study revealed that the simultaneous utilization of inulin and whey protein isolate as carrier agents resulted in the highest stability, compared with whey protein or inulin alone. 92 However, the most applied technique to encapsulate of betalains is spray-drying, because this technique is characterized by low price, simple processing, as well as short time to obtain encapsulated betalains, but the matrix of this method has high solubility in the solvents, which could readily evaporate at high temperature, and some bioactive compounds might suffer from degradation due to high temperature.…”
Section: Processing Of Red Beetroot Betalainsmentioning
confidence: 99%
“…After contacting with hot air during spray drying, whey protein can instantly form a film around the particle and avoid the possible adhesion of low-molecular-weight compounds occurring in the beetroot to the drying chamber walls . Inulin could also act as a carrier agent, and its use has become increasingly popular in recent years . Moreover, a previous study revealed that the simultaneous utilization of inulin and whey protein isolate as carrier agents resulted in the highest stability, compared with whey protein or inulin alone .…”
Section: Processing Of Red Beetroot Betalainsmentioning
confidence: 99%
“…Multiple chloroquine emulsions, an antimalarial drug, have been successfully made and proven to effectively disguise the bitter taste. [43][44][45][46] Taste masking of chlorpromazine, an antipsychotic drug, has also been reported by multiple emulsions.…”
Section: Taste Maskingmentioning
confidence: 99%